Le travail scolaire : définition, histoire et moteu d’un objet d’étude socio-historique - Nicolas Sembel (Recherches en Éducation)
The aim of this paper is to build the school work as a socio-historical object. While academic work is often perceived as "what the school wants" from students (effective, it enables students to succeed; ineffective, it led to failure), it should rather be defined to a sociological perspective, as the report of students to what school wants. School work would then consist of all that is done by students, more or less in line with the framework and requirements school, which is of an intellectual work. The sociological approach highlights a tension constitutive of school work so defined, criticizing its institutional history to highlight its history "from below" by the actual practices of students and their actual interactions with the school institution, which it is also redefined. When replacing then this sociological approach in a historical perspective, it is possible to formulate a socio-historical hypothesis, that the engine of school work is a product of anthropological tension, standing in the long term, between the actor and the system. The school work as a socio-historical object of research feeds the opposition between the economy of the simplification of learning, which tends to "naturally" any educational institution, when the resistances are not too strong, and the economy of subjectification through work, which also tends "naturally" the student, when the school selection is not too strong. School work redefined socio-historically is structured around the opposition between intellectual interest and intellectual competition. It produces, among other things, a unique historical figure: an "heretic" school worker, characterized by a special relationship of autonomy to the school institution, the "conflictual disengagement" (Eigensinn).